2017
DOI: 10.7220/2345-024x.20.2
|View full text |Cite
|
Sign up to set email alerts
|

The changes of self-efficacy and perceived social support of addicted to alcohol women and men during treatment period

Abstract: Abstract. Background. In order to develop an effective alcohol and other psychoactive substance use prevention programs and improving addiction treatment methods, it is useful to determine the evolution of specific psychological factors of addiction disease during treatment. The aim of the research is to determine the changes in selfefficacy and perceived social support of alcohol-addicted men and women during the treatment. Results. The overall self-efficacy, drinking refusal self-efficacy and perceived socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…A study conducted to see the status of self-efficacy and perceived social support of 101 alcohol-dependent subjects in Kansas county center for addictive disorders after treating them through Minnesota 12-step program concluded that the overall self-efficacy, drinking refusal self-efficacy and social support of alcohol-dependent women and men at the end of treatment was higher than at the beginning of treatment which supports our finding. [ 18 ] A study conducted to examine the impact of MI on self-efficacy, motivation, and outcome expectancies in adolescents. The finding depicts that the intervention assisted in the behavior change in the positive way indicates an enhancement in motivation and abstinence from the use of substance, also an increase in the self-efficacy to be able to ignore the addictive agent.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted to see the status of self-efficacy and perceived social support of 101 alcohol-dependent subjects in Kansas county center for addictive disorders after treating them through Minnesota 12-step program concluded that the overall self-efficacy, drinking refusal self-efficacy and social support of alcohol-dependent women and men at the end of treatment was higher than at the beginning of treatment which supports our finding. [ 18 ] A study conducted to examine the impact of MI on self-efficacy, motivation, and outcome expectancies in adolescents. The finding depicts that the intervention assisted in the behavior change in the positive way indicates an enhancement in motivation and abstinence from the use of substance, also an increase in the self-efficacy to be able to ignore the addictive agent.…”
Section: Discussionmentioning
confidence: 99%